Analisis Kemampuan Pemahaman Matematis Pada Siswa Slow Learner - Imam Tantowi Afan; Wikan Budi Wikan; Eleonora Dwi Wahyuningsih (Jurnal Inovasi Pendidikan Matematika (JIPM), 2021)
This study aims to describe how the mathematical understanding ability ofstudents slow learner in solving simple algebra problems and what are the factors that causestudents to have slow learner difficulty understanding and solving math problems in class V SD Negeri Randusanga wetan 01 Brebes. This research method is a qualitative research, the approach in this study uses a descriptive approach. The research subjects were slow learner grade 5 students at SD Negeri Randusanga Wetan 01 Brebes. Data collection techniques using documentation, tests and interviews. The results of the study stated that thestudents slow learner did not meet the indicators of mathematical understanding ability, the factors causing thestudents to have slow learner difficulty understanding the questions were internal factors and external factors. Internal factors, very low student discipline, low intelligence limitations of students,. External factors are the economic limitations of the subject's parents which make the subject lazy and have no motivation to learn. Then, the facilities at the school are lacking, so teachers in the learning process rarely use learning media or teaching aids.